Conceção, planeamento e operacionalização de uma época desportiva de nadadores juvenis e juniores do Futebol Clube do Porto - Sergio Baptista da Silva (2016)
The Conception, planning and production of scientifically based training ,were the main purpose of this work during the sportive season 2015/2016. In order to accomplish the whole process a close correlation of concepts has been established, between the practice of training in general, swimming training (more specifically) namely the competion performance, the performance of young swimmers, their coach and many other essential concepts. The aim of this work is to present a reasoning upon the theory and methodology of swimming training, focusing on the decisions taken throughout the season. The approach is made in three phases, three Macrocycles, with a Group of swimming hopes (mainly constituted by juveniles,but also juniors and one senior swimmer, that couldn't achieve the score established by the Club to take part of the main team). FCP Team ,composed by 17 swimmers, has achieved the following results: * 49 personal records in North Zonal Championships; * 129 personal records in Regional Championships; * 57 personal records in Meetings; * 59 personal records in National Championships; * 26 Regional Titles (56 total podiums); * 2 National Titles (both by relay/4 total podiums).